2020
DOI: 10.3346/jkms.2020.35.e244
|View full text |Cite
|
Sign up to set email alerts
|

Audiologic Status of Children with Confirmed Cytomegalovirus Infection: a Case Series

Abstract: Background: Congenital cytomegalovirus (CMV) infection is the most common non-genetic cause of sensorineural hearing loss (SHNL) in children. Only about 10% to 15% of children with congenital CMV are symptomatic, and most are not diagnosed at birth. About 7% to 15% of clinically asymptomatic patients may develop later complications, including SNHL, which is the most common sequela in clinically asymptomatic patients. In this study, hearing status was investigated in children with confirmed CMV infection and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“… 36 Hearing loss may not be present at birth but later progression or fluctuation of hearing have been noted. 37 38 Recent study conducted in Korea proposed the clinical significance of CMV diagnostic test after 3 weeks from birth in children with SNHL. 39 However, the clinical utility of diagnostic strategy is needed to be examined in further research.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Hearing loss may not be present at birth but later progression or fluctuation of hearing have been noted. 37 38 Recent study conducted in Korea proposed the clinical significance of CMV diagnostic test after 3 weeks from birth in children with SNHL. 39 However, the clinical utility of diagnostic strategy is needed to be examined in further research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fletcher et al ( 15 ) found a wide variance (9–68%) in onset time of SNHL based on information from 36 previous studies. In a retrospective case study by Kim et al ( 16 ), 11 out of 58 children (19%) with cCMV had SNHL, but the majority of them were not identified as having hearing loss (HL) during the hospital hearing screening, suggesting SNHL can occur later in life for this population even after passing a newborn hearing screening. Demmler-Harrison et al ( 14 ) studied the long-term effects of cCMV-related HL, finding 20% of asymptomatic cCMV cases born with normal hearing to have late-onset SNHL.…”
Section: Discussionmentioning
confidence: 99%